Health Literacy Regarding Sodium Consumption of Undergraduate Students in the Lower Northern Region, Thailand - Youngiam, Waraporn; Abdullakasim, Pajaree; Maharachpong, Nipa (Naresuan University Journal: Science and Technology (NUJST), 2022)
At present, the sodium intake of Thai youth is about twice as high as recommended. Health literacy has been confirmed to be an important factor in disease prevention, health promotion, and quality of life improvement. However, few studies have concentrated on the sodium health literacy among university students. This cross-sectional survey study aimed to describe health literacy regarding sodium consumption of undergraduate students in the lower northern region of Thailand and to identify factors affecting the students’ sodium consumption behaviors. An online self-administered questionnaire was used to collect data from 395 first-year students of a selected university. Binary Logistic Regression (BLR) was performed to analyze factors affected high sodium consumption behaviors. Results of the study revealed that, most of the students were female (68.6%), age over 18 years old (61.6%), studied in non-health science areas (74.0%). The number of students who had underweight and obese were similar (28.6% and 26.3%, respectively). Approximately half of participants were self-cooking (52.9%), and eating late at night (55.2%). Most of them love spicy taste food (74.4%) and using social media about food (81.0%). Regarding health literacy about sodium consumption, majority of the students (79.5%) had low cognitive skills; they had moderate skills on accessibility to information (44.6%), communication (55.9%), self-management (49.1%), and media literacy (44.1%); and had high decision-making skills (44.6%). Results of the BLR analysis using enter method showed the characteristic factors of the students that affected their high sodium consumption behaviors (OR>1.0) were love to eat spicy taste food (OR=2.20; 95%CI: 1.18-4.09) followed by had underweight BMI (OR=2.12; 95%CI: 1.17-3.85), and male students (OR=1.95; 95%CI: 1.16-3.28). When health literacy regarding sodium consumption were considered, low communication skills had the highest affected on high sodium consumption behaviors (OR=3.08; 95%CI: 1.33-7.10) followed by low cognitive skills (OR=2.35; 95%CI: 1.18-4.80). In order to reducing high sodium consumption behaviors of the youth, health literacy about sodium consumptions should be enhanced through behavioral modification program specifically communication skills and cognitive skills. Additionally, students who love to eat spicy taste food should be emphasized. This result provides factors affected to high sodium consumption behaviors should be considered for interventions to reduce high sodium consumption among university students. Keywords: Health literacy, sodium consumption, undergraduate students, Thailand